2022
DOI: 10.1002/mame.202100686
|View full text |Cite
|
Sign up to set email alerts
|

A Facile and Flexible Humidity Sensor Based on Porous PDMS/AgNWs and GO for Environmental Humidity and Respiratory Detection

Abstract: Humidity sensors, benefit from their superior humidity-sensitive components, are able to respond to the environment moisture changes. Based on this feature, the humidity sensor plays an increasingly vital role in biological detection. To improve the performance of humidity sensors, a large number of optimizations have been made from several aspects, such as material synthesis and structural design. In this study, a novel humidity sensor is designed to increase its specific surface area to carry more humidity-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The more common approach relies upon the deposition of a second, moisture-sensitive layer via drop casting, spraying, etc. [33,35,36,45]. A pertinent example is the work by Lan and colleagues (2020), where lasered graphene electrodes coated with graphene oxide were employed to facilitate measurement of stomatal moisture dynamics on leaves [45].…”
Section: Design Requirements and Sensing Methodologiesmentioning
confidence: 99%
“…The more common approach relies upon the deposition of a second, moisture-sensitive layer via drop casting, spraying, etc. [33,35,36,45]. A pertinent example is the work by Lan and colleagues (2020), where lasered graphene electrodes coated with graphene oxide were employed to facilitate measurement of stomatal moisture dynamics on leaves [45].…”
Section: Design Requirements and Sensing Methodologiesmentioning
confidence: 99%
“…For instance, Yuan et al [17] fabricated PEDOT:PVMA humidity sensor using inkjet-printing on a paper substrate that exhibited the sensor response of 71%-98% to exposure in air with humidity changing in range of 11%-97% RH at room temperature. Ma et al [18] reported that flexible humidity sensor based on porous PDMS/AgNWs and GO can detect the humidity with a wide range of 8.6-93 RH% in a fast response with high sensitivity. Hashim et al [19] introduced polyvinyl alcohol (PVA)-polyethylene oxide (PEO)copper oxide (CuO) nanocomposites as sensitive materials to be resistive humidity sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Surface micro/nanostructures detection is of great significance in broad research fields, such as biomedical [1,2], environmental monitoring [3], micro-nano optics [4], and so on. The common surface micro/ nanostructures detection methods contain laser interferometry [5], scanning probe techniques [6], scanning electron microscopy [7,8], scanning near-field microscopy [9], and Raman spectroscopy [10].…”
Section: Introductionmentioning
confidence: 99%